Wicked Words and Illegal Imaginings: A Genealogy of Obscenity In Which a Criminological Case Study of Fanny Hill Is Conducted - Piamonte, Stephanie (Université d'Ottawa / University of Ottawa, 2019)
A genealogy of the concept of obscenity is conducted through a case study of John Cleland’s novel, "Memoirs of a Woman of Pleasure" (1748-1749), popularly known as "Fanny Hill". Analytic attention is focused on events (i.e. given moments in history characterized by struggle), discourses (i.e. systems of knowledge), and practices (i.e. institutional procedures), all of which are interrelated, and problematizes them with a moral regulation interpretive framework. This dissertation considers how "Fanny Hill" was (re)problematized as obscene through historically specific discursive practices, and how these discursive practices, conceived as the exercise of power in conjunction with systems of knowledge or as projects of moral regulation, had effects on the constitution of subjectivities and social orders. Further, this dissertation problematizes the ways that these discourses, practices and effects – particularly those pertaining to harm – continue into the present.
Keywords: Fanny Hill; obscene; literature; genealogy; moral regulation; criminology